(untitled) (Training and Practice : Journal of Educational Sciences, 2016)
Health, complete life! The most depressing and the most difficult situation in life is when a child becomes seriously ill. Then you revalue everything in a matter of moments, and you cannot think about anything but to be healthy again, or at least have a complete and bearable life with your disability. Pedagogy of hospital, hospital and pedagogy. All of us have already met these two words separately, but what does pedagogy of hospital mean as a collocation? Only a few people know this term and only a few people have heard about it. However, this term exists and it plays an important role in sick children’s life. Now we would like to discuss the following terms ’pedagogy of hospital’ and ’hospital teachers’. We will get to know the origins of pedagogy of hospital. We will find out where it is from, where it is now and how it is developing nowadays in Hungary. In this study we intend to highlight why the pedagogy of hospital is important in several aspects. We also want to point out that this is a very complex field of pedagogy.